Technologies used in critical care in combating Covid-19: Scope review (Research, Society and Development, 2021)
Objective: to search the scientific literature for technologies to be used by nursing professionals in high complexity care to combat the disease caused by the new Coronavirus (SARS-Cov2). Method: review in the scoping review format based on the procedures recommended by the Joanna Briggs Institute. Mapping was carried out on the bases of white and gray literature, in a timeless cut and without language limitation. The study selection design followed two screenings in order to reduce bias. The included studies were presented as narrative summaries and tables. Results: 680 publications were mapped, of which four studies were selected because they met all the inclusion criteria. The most relevant findings involve the use of ultraviolet light, radiation, extracorporeal membrane oxygenation and portable echocardiograms. Conclusion: there were few, but promising, technologies studied for use in highly complex assistance to patients with COVID-19, showing a needy and favorable field for research.